Justifying pension reforms: Comparing policy discourses in Norway and the UK. Issue 3 (September 2020) - Ring, Patrick; Ervik, Rune; Lindén, Tord Skogedal
The latest UK and Norwegian state pension reforms have reflected contrasting policy design in the balance of private pensions, savings and state provision. Nevertheless, we argue that both governments have in many ways adopted strikingly similar approaches in seeking public acceptance of these potentially controversial reforms, employing a similar repertoire of discursive elements to persuade populations about their logic and rationality. Based on critical analysis of government policy papers, speeches and parliamentary debates, we find that both countries emphasise 'sustainability' and 'fairness' within an increasingly individualised context where both systems are characterized as facilitating individuals' efforts to attain security in retirement through 'choice' or 'flexibility'. Significantly, contrasting symbolic metaphors are adopted to situate these reforms, and their proponents, within the heritage and traditions of their different welfare systems, which we find is a key element in successfully implementing the reforms. We note the implications of this research for the analysis of European state pension reform.